DETERMINANTS OF HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH CHRONIC KIDNEY DISEASE: A COMPREHENSIVE ANALYSIS OF DEMOGRAPHIC, CLINICAL, AND BEHAVIORAL FACTORS - Ruku, Denny Maurits (Fakultas Keperawatan, Universitas Klabat, 2026)
ABSTRACT Chronic kidney disease (CKD) significantly impairs health-related quality of life (HRQOL); however, global evidence regarding its determinants remains limited and fragmented. This study aimed to examine the combined effects of demographic, clinical, and behavioral factors on HRQOL among individuals with CKD. A cross-sectional study design was employed using secondary data obtained from the Kaggle dataset, involving 1,524 participants. HRQOL was analyzed in relation to demographic characteristics, clinical indicators, and behavioral factors. Statistical analyses included descriptive statistics, Pearson correlation, independent t-test, one-way ANOVA, and multiple linear regression. HRQOL was significantly negatively correlated with age (r = −0.58), body mass index (r = −0.06), alcohol consumption (r = −0.92), systolic blood pressure (r = −0.45), fasting blood sugar (r = −0.31), total cholesterol (r = −0.28), and low-density lipoprotein (LDL) (r = −0.23). In contrast, HRQOL was positively associated with physical activity (r = 0.98) and high-density lipoprotein (HDL) (r = 0.40). No significant associations were observed with gender, ethnicity, education level, or diabetes status. In multivariate analysis, physical activity emerged as the strongest positive predictor (β = 0.75, p < .001), while alcohol consumption was the strongest negative predictor (β = −0.18, p < .001), alongside age, diastolic blood pressure, total cholesterol, and LDL. The final model explained 97.8% of the variance in HRQOL (R² = 0.978). HRQOL in CKD is influenced by a complex interplay of demographic, clinical, and behavioral factors, with behavioral factors—particularly physical activity and alcohol consumption—playing a dominant role. An integrated, patient-centered approach is essential to improve HRQOL outcomes in this population. Penyakit ginjal kronis (PGK) secara signifikan memengaruhi health-related quality of life (HRQOL), namun bukti yang ada mengenai faktor prediktornya masih terbatas secara global. Tujuan penelitian ini untuk mengkaji pengaruh gabungan dari faktor demografis, klinis, dan perilaku terhadap HRQoL pada individu dengan PGK. Desain Cross sectional study dilakukan menggunakan data sekunder dari Kaggle, yang melibatkan 1524 peserta. HRQOL dianalisis dalam kaitannya dengan karakteristik demografis, indikator klinis, dan faktor perilaku. Analisis statistik deskriptif, Pearson correlation, t-test, ANOVA, dan multiple linear regression digunakan dalam analisis. HRQOL secara signifikan negative terkait dengan usia (r = -0,58), index masa tubuh (r = 0,05), konsumsi alkohol (r = -0,92), systolic (r = -0,45), fasting blood sugar (r = -0,31), cholesterol (r = -0,28), low-density lipoprotein (LDL) (r = -0,23); Sedangkan HRQOL positive significant dengan aktifitas fisik (r = 0,98), dan high-density lipoprotein (HDL) (r = 0,40); Namun, tidak memiliki hubungan yang significant dengan jenis kelamin, etnis, education, dan Riwayat diabetes. Dalam analisis multivariat, aktivitas fisik muncul sebagai prediktor positif terkuat (β = 0,75, p < 0,001), selain systolic, FBS, HDL dan trigliseride; Sedangkan konsumsi alkohol (β = -0,18, p < 0,001) merupakan predictor negative terkuat selain usia, diastolic, cholesterol, LDL yang merupakan predictor dari HRQOL pasien PGK. Model akhir menjelaskan 97,8% varians dalam HRQOL (R² = 0,978). HRQOL pada PGK dipengaruhi oleh kombinasi faktor demografis, klinis, dan perilaku, dengan aktivitas fisik memainkan peran dominan. Pendekatan terintegrasi sangat penting untuk meningkatkan hasil yang berpusat pada pasien.